Komunitas Mamalia Kecil Terestrial di Gunung Singgalang, Sumatera Barat - Heru Handika; - Jabang; - Rizaldi (Universitas Andalas, 2013)
The communities of small terrestrial mammals are known to be affected by the forest disturbances. The investigation of small terrestrial mammals’ community in had been conducted Mount Singgalang, West Sumatra, Indonesia. Small terrestrial mammals were trapped in three different habitats; heavily disturbed, slightly disturbed and undisturbed forest. At each site, four transects were established using a total of 360 trap-night effort (120 trap-nights effort per site). We caught 37 individuals, consisted of 8 species which were included into 3 families and 3 orders. Composition and structure of the community was different among habitats.The highest diversity and abundance was found at slightly disturbed forest. In term of species composition, heavily disturbed forest was more similar to slightly disturbed forest than undisturbed forest. Crocidura neglecta and Maxomys surifer were the most tolerant species to the effect of forest disturbance. It is concluded that such differences among habitats in Mount Singgalangtend to have certain influences, although the significant difference was not found.Keywords: community, small terrestrial mammals, Mount Singgalang